Influence of Kautilya’s Philosophy in Prithvi Narayan Shah’s Unification Campaign - Bista, Prakash (Journal of APF Command and Staff College, 2025)
Before Prithvi Narayan Shah, the King of Gorkha, found out the possibilities of solidifying Gorkha kingdom, Nepal was divided into many smaller states. Although his statecraft shows his strategic acumen in winning and consolidating states to formally make a unified Nepal there is a gap in academia about the the source of the strategies applied by him.This paper has examined the unification strategy and statecraft of Prithvi Narayan Shah, the founder of modern Nepal, through the lens of Kautilya’s ancient wisdom portrayed in the Arthashastra and seeks to uncover the possible influence of Kautilyan principles on his strategies. This qualitative research design based on secondary sources explored the historical context of Prithvi Narayan Shah’s reign and the political landscape of 18th-century Nepal. It argues that Prithvi Narayan Shah’s methods of diplomacy, military conquests, and internal administration resembles key aspects of Kautilya’s teachings provided in Arthashastra specifically the Mandala Theory as a defense strategy. The paper based on exploratory research design with comparative study of Kautilya’s philosophy and Prithvi Narayan Shah’s strategies has found out that there are tactical similarities with Kautilya’s ideas and Prithvi Narayan Shah’s approach during the unification.